Are two gluons the QCD Pomeron? - Éboli, O. J. P. [UNESP]; Gregores, E. M.; Halzen, F. (American Physical Society (APS), 1998)
Collider experiments have recently measured the production cross section of hard jets separated by a rapidity gap as a function of transverse momentum and gap size. We show that these measurements reveal the relative frequencies for the production of rapidity gaps in quark-quark, quark-gluon and gluon-gluon interactions. The results are at variance with the idea that the exchange of two gluons is a first order approximation for the mechanism producing colorless states, i.e. the hard QCD Pomeron. They do qualitatively support the soft color or color evaporation scheme developed in the context of bound-state heavy quark production.